Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Skincare Aloe Vera XYZ di Kota Pontianak - Eva Mulia Saputri; Eva Dolorosa; Wanti Fitrianti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The skincare sector has many prospects due to the growing public awareness of skin health. Indonesia's cosmetics industry grew by 20.6% between 2021 and 2022, according to data from the Food and Drug Supervisory Agency (BPOM). The XYZ skincare products, which originated in Pontianak City, West Kalimantan, and are derived from aloe vera, are among the most well-liked items from this trend. This study examined how the marketing mix impacted Pontianak City's purchases of O-degree products. Pontianak City was chosen for this study because it is a hub for aloe vera farming and is renowned for generating high-quality goods. The study's sample size was 100 customers aged 17 and older who had bought skincare products containing aloe vera at least twice in the previous six months. The factors influencing purchase decisions are assessed using the data analysis technique known as structural equation modeling (SEM). Product, pricing, location, and advertising were the characteristics that were being examined. The survey's results showed that most participants were female, between the ages of 21 and 25, working for a private company, college-educated, and making between Rp1,500,001 and Rp3,000,000. The product variable influenced consumers' buying decisions the most of the four factors analyzed. This is due to the distinctive worth and uniqueness of XYZ items, which are native Pontianak commodities. To improve buying decisions, entrepreneurs must focus more on improving product quality and maintaining the features that are the product's main draws. By enhancing product quality and giving local Pontianak products more prominence, XYZ is expected to be able to compete more successfully in the fiercely competitive skincare market.